Comparative Study of Efficacy and Safety of Diacerein versus Acelofenac in Patient with Knee Osteoarthritis - Sharma, Sashmit; Rijal, Kiran Prasad; Prasai, Tanup; Khanal, Himal (Nepal Journal of Medical Sciences, 2021)
Introduction: There are different pharmacological modalities currently in practice for the treatment of osteoarthritis knee. Broadly these are divided into anti-inflammatory drugs such as NSAIDs and symptomatic slow-acting drugs in osteoarthritis (SYSADOA). Diacerein, an anthraquinone derivative inhibits IL-1b and has been shown to significantly decrease the symptoms. Methods: This is open label, prospective comparative study. Total 40 patients were divided into two groups: group A (diacerein) and group B (aceclofenac) by alternate method. In group A diacerein was given 50mg orally for 1 week followed by 50 mg orally twice a day for 3 weeks. In group B aceclofenac 200 mg sustained release tablet was given orally once a day for 4 weeks. Outcomes were measured at the end of the treatment period i.e. at four weeks and after two weeks of discontinuation of treatment i.e. at 6 weeks. Results: Improvement is observed in both treatment groups in their baseline value in terms of efficacy parameters. Results of VAS and WOMAC scores were better in group B (aceclofenac). However intra-group analysis showed VAS scores and WOMAC scores significantly decreased in patients receiving diacerein as well. (p<0.05). Conclusion: Though not superior to the control drug, diacerein showed efficacy in terms of measurement by patient self-reported WOMAC and VAS scores for the treatment of Osteoarthritis knee.